Exploration of Barriers and Strategies for Implementing Green Information System at the Directorate of Information Technology Universitas Brawijaya - Intan Sartika Eris Maghfiroh; Ismiarta Aknuranda; Robin Yustan (Faculty of Computer Science Universitas Indonesia, 2025)
This study explores user perceptions of Green Information Systems (GIS) at the Directorate of Information Technology (DTI), Universitas Brawijaya, and identifies strategies for enhancing GIS adoption using the Persuasive System Design (PSD) framework. Data were collected through semi-structured interviews with four employees from various roles, including system administrators and managerial staff. Using thematic analysis and coding processes (open, axial, and selective), findings reveal positive perceptions of GIS, particularly in energy management through server virtualization, document digitalization, and e-waste management. However, challenges such as the absence of formal policies, central regulations hindering digitalization, and a lack of automated energy monitoring persist. Recommended strategies include automated sleep modes integrated with cybersecurity education, regulatory advocacy for digitalization, and campaigns on e-waste management. The integration of Green IS with cybersecurity offers an innovative approach to accelerate GIS adoption while improving data protection, supporting sustainable IT operations at DTI Universitas Brawijaya.